Differential fault attack on lightweight block cipher Klein - Yong-juan WANG; Quan-yu2 REN; Shi-yi ZHANG (Tongxin xuebao)
As a lightweight block cipher algorithm based on SP structure,Klien has the characteristics of high efficiency and low energy consumption.By analyzing the S-boxes differential propagation path,it was found that under the condi-tion of same input and different difference,the intersection elements were unique,which fall in the intermediate state set corresponds to output difference,and a differential fault attack scheme was proposed.By injecting two different faults in the last round of the algorithm,all the keys of the Klein algorithm can be recovered,and the complexity is negligible.This method can be promoted to other block cipher algorithms based on SP structure and Feistel structure.